Influence of Brazilian red propolis polymeric nanoparticles in haematology, renal, and hepatic evaluations in dogs (Research, Society and Development, 2020)
Recognized for various beneficial actions, propolis can be differentiated according to its origin. Red propolis, discovered in the northeast of Brazil, offers a strong antioxidant action. Nanoparticles are an innovative tool in the pharmaceutical field, as they help in efficient drug delivery. This study aimed to use red propolis nanoparticles in dogs and evaluate their action based on hematological and biochemical results. Eight healthy adult dogs (bodyweight, 6–27 kg) received 50 mg/animal of polymeric nanoparticles with 20% red propolis extract in a capsule, orally, once a day. Blood samples were collected weekly (five times), and hematologic, hepatic, and renal evaluations were performed. No significant changes were observed, except for alkaline phosphatase, which showed a significant reduction over time. This study in healthy adult dogs did not verify any hematologic, renal, or hepatic adverse effects of daily oral red propolis polymeric nanoparticles (capsules) administration. The results suggest a potential beneficial effect on the liver.